ANALISIS NILAI FEMINISME TOKOH HIGUCHI ICHIYO DALAM NOVEL CATATAN ICHIYO KARYA KIMURA REI - PUTRI, SISKA NOVALIA (Jurnal Ilmiah Mahasiswa FIB, 2013)
A Note From Ichiyo Novel is a novel written by Kimura Rei. It tells about a woman of letter journey in Meiji era. Higuchi Ichiyo met a lot of obstacles to make her dream come true as a writer. The refusal in Meiji era did not break Ichiyo’s passion to be a writer. A Note From Ichiyo Novel shows that Ichiyo has feminism values. That’s why, this research is analized how feminism value is had by Higuchi Ichiyo. This research uses feminism values approach according to Arimbi Heroepoetri and R. Valentina Sagala. There are four feminism values that the research used to analys i.e : personal power, creativity, equivalence, and autonomous ecoomic. The result of this research shows that Higuchi Ichiyo had feminism value in her strunggle to be a writer in Meiji era. Her personal power made Ichiyo could formulate about herself. The creativity in writing made Ichiyo had special characters amoung others writers. Besides, Ichiyo could be equal herself with man at the moment. Her autonomous economic in did her profession made Ichiyo could hold out in her simplicity. The writer suggestd to the next researcher to research using literatur psycological approach, or historical approach in A Note From Ichiyo.   Keyword : Figure, Higuchi Ichiyo, Japanese Woman, Meiji, Feminism Value